2011
DOI: 10.5248/116.217
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of spore ornamentation in Laccaria tortilis (Basidiomycota, Agaricales)

Abstract: -"Laccaria tortilis" sensu Clémençon 1984 is described as the new form, Laccaria tortilis f. clemenconii, based on material from Kamchatka (Asiatic Russia), Switzerland, Austria, and Italy. ITS rDNA analysis indicates that the new form is molecularly identical to Laccaria tortilis, although smaller spores with shorter spines distinguish it morphologically. Scanning electronic micrographs of the spores and a dichotomous key to European Laccaria species with mono-bisporic basidia, are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, Mueller and Vellinga (1986) and Mueller (1992) found that the type specimen of L. ohiensis possess exclusively tetraspored basidia, suggesting that any Laccaria with bisporic basidia should be treated as a separate species. According to Mueller (1992), in the Americas there are 3 species of Laccaria with bisporic basidia: L. fraterna, L. pumila Fayod and L. tortilis (Bolton) Cooke, which are phylogenetically related (Vizzini et al 2011). The latter 2 species are similar to L. fraterna due to the presence of bisporic basidia, in addition to a few shared macroscopic…”
Section: Discussionmentioning
confidence: 99%
“…However, Mueller and Vellinga (1986) and Mueller (1992) found that the type specimen of L. ohiensis possess exclusively tetraspored basidia, suggesting that any Laccaria with bisporic basidia should be treated as a separate species. According to Mueller (1992), in the Americas there are 3 species of Laccaria with bisporic basidia: L. fraterna, L. pumila Fayod and L. tortilis (Bolton) Cooke, which are phylogenetically related (Vizzini et al 2011). The latter 2 species are similar to L. fraterna due to the presence of bisporic basidia, in addition to a few shared macroscopic…”
Section: Discussionmentioning
confidence: 99%